Pregnant Women And Families' Readiness Towards The Implementation Of Exclusive - Fitriani, Aida; Us, Hafsah; Agustina, Fitriani; Erlina, Erlina; Friscila, Ika (JKM (Jurnal Kebidanan Malahayati), 2025)
Latar Belakang: Tingginya angka bayi yang telah diberi MPASI sebelum berusia 6 bulan menyebabkan rendahnya pencapaian ASI eksklusif. Pemberian ASI eksklusif sampai 6 bulan dan dapat dilanjutkan sampai usia 2 tahun juga mendapat perhatian serius dari pemerintah dan kembali dituangkan dalam Kepmenkes RI. No.450/MENKES/IV/2004.Tujuan: Mengetahui kesiapan ibu hamil dan keluarga terhadap penerapan ASI Eksklusif di wilayah kerja Puskesmas Peusangan Siblah Krueng.Metode:  Metode penelitian menggunakan rancangan observasi analitik dengan desain penelitian cross sectional. Sampel penelitian menggunakan teknik total sampling berjumlah 30 orang. Pengumpulan data menggunakan kuesioner. Uji bivariat menggunakan Fisher's Exact Test.Hasil: Berdasarkan analisis statisti didapatkan bahwa ada hubungan kesiapan ibu hamil (0,000) dan keluarga (0,049) terhadap penerapan ASI Eksklusif di wilayah kerja Puskesmas Peusangan Siblah Krueng.Kesimpulan: Ada hubungan kesiapan ibu hamil dan keluarga terhadap penerapan ASI Eksklusif di wilayah kerja Puskesmas Peusangan Siblah Krueng.Saran: Diharapkan dapat sebagai bahan untuk terus memberikan memperbaharui pengetahuan ASI eksklusif sehingga ibu hamil dan keluarga dapat bersinergi hingga penerpan ASI eksklusif. Kata Kunci : ASI Eksklusif, Kesiapan Ibu Hamil, Kesiapan Keluarga. ABSTRACT Background: The majority of women who marry before the age of 18 come from poor families and are below the poverty line, according to statistical data 28.10% of teenagers marry before the age of 18 and give birth to their first child at the age of 15-19 years.Purpose:  Analyzing why and what causes early marriage among Acehnese teenagers in Lhokseumawe City.Methods:  Qualitative research with an interpretive model to analyze early marriage among young women. The study was conducted in the city of Lhokseumawe. The researchers studied the cases of three people who married early. Data analysis was carried out by grouping people and events according to their characteristics according to categories and chronological order.Results: The results of the study showed that the causes of early marriage in Lhokseumawe city are due to local community habits, young women no longer attend school, are afraid of committing crimes (adultery), getting married (loving), premarital pregnancy and lack of knowledge about reproductive health.Conclusion: To reduce early marriage, every young person must undergo 12 years of compulsory education to reduce the high rate of early marriage and reduce the interest of young people to marry at a young age.Suggestions; Conducting counseling and socialization about the ideal age for marriage routinely and continuously and in synergy with related agencies. Keywords: exclusive breastfeeding, pregnant mother readiness, family readiness